(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The studies based on systematic isotope variations in carbonate rocks are valuable tools to understand the evolution of marine sedimentary basins, especially those developed during a key Earth history time such as the Neoproterozoic-Lower Paleozoic, interval from which fossil register is incomplete. The isotopic data allow to gather important information about sedimentation- diagenetic ages, metamorphic events, tecto-sedimentary paleoenvironments evolution, sedimentary provenance and source areas. In particular, determining the Sr and C isotopic rate in non-fossiliferous carbonates is very important because it provides the precipitation age indirectly and can be applied for stratigraphic correlation in local and regional scale as well. On the other hand, the Sm-Nd isotope ratios on sedimentary rocks are useful because they allow learning about the basement type rocks of the basin and the possible source regions. The present contribution reports stable isotope studies (C and O), natural 87Sr/86Sr, 206Pb/207Pb and Sm- Nd ratios obtained on carbonate rocks outcropping in the Precordillera-Cuyania terrane (Astini et al., 1995; Ramos et al., 1998) from western Argentina. The main object of this work is to increase the isotopic database about low metamorphic carbonates that crop out in the Western Sierras Pampeanas, assigned by several authors as Neoproterozoic- Lower Paleozoic units, and furthermore, we compare the obtained results with well known fossiliferous Cambrian limestones from the Eastern Precordillera. The analysed rocks are non-fossiliferous metalimestones, marbles, and meta-marls of the Caucete Group (Sierra de Pie de Palo); carbonates with low metamorphism outcrop in Cerro Salinas and Sierra de la Huerta (Pan de Azúcar and Loma de las Chacras). For comparison, Cambrian fossiliferous limestones (no metamorphic) were studied from La Laja Formation (Sierra Chica de Zonda, Precordillera of San Juan). Sr isotopic data from Caliza Angacos (Sierra de Pie de Palo) are in agreement with the published secular variation curve for the Lower Cambrian and partially Middle Cambrian. The d13C values for the same unit are spread in the C secular variation curve in coincidence with the 87Sr/86Sr ratios (Fig. 10). 13C/12C and 87Sr/86Sr ratios obtained from samples from Juan Pobre Member of La Laja Formation are positioned on the Middle Cambrian interval in agreement with their fossiliferous content (Fig. 10). The Cerro Salinas carbonates show higher 87Sr/86Sr ratios in comparison with the Caliza Angacos (Sierra de Pie de Palo) and in concordance with the Late Middle Cambrian to Upper Cambrian isotopic curve (Fig. 10). The increasing Sr isotope ratios are positioned on the youngest sector of the Upper Cambrian on the secular variation curve for sea-water. This event is in concordant with the isotopic global positive excursion (Montañez et al., 2000). The 207Pb/206Pb isochrone, obtained for the limestones of Cerro Salinas, suggests an age on the boundary of Neoproterozoic and Cambrian time. The presence of stromatolites and the isotopic Sr composition on the Cerro Salinas carbonate unit could be correlated with the La Flecha Formation (Upper Cambrian of Precordillera). Nd model ages (TDM) measured for the siliciclastic levels intercalated in the Soldano Member (La Laja Formation) are coincident with the Caliza Angacos (Pie de Palo). This suggests that the provenance area for this formation and the fossiliferous Lower Cambrian units from Eastern Precordillera are similar. In the frequency diagram (Fig. 9) the source rocks from these sediments present two well differentiated populations for the Nd model ages: Paleoproterozoic (1.7 Ga) and Mesoproterozoic (1.5 Ga). Isotopic evidences allow us to interpret that the marine carbonates analyzed in this work could be part of the common carbonate platform during Cambrian times, registering deeper water sedimentary conditions and increasing metamorphism towards the East.